An experimental test of direct and indirect reciprocity in case of complete and incomplete information - Martin Dufwenberg; Uri Gneezy; Werner Güth; Eric E. C. van Damme (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
Direct reciprocity means to respond in kind to another person whereas indirect reciprocity is understood here as rewarding someone else. We perform corresponding experiments which use a similar underlying structure as the reciprocity experiment of Berg, Dickhaut, and McCabe (1995). Another variation concerns the information about the multiplier of donations where we compare the benchmark case with a commonly known multiplier to a condition where the multiplier is known for sure only by donators. Questions which we try to answer are: Will indirect reciprocity induce higher or lower donations?, will donators with the high multiplier hide behind the small one?, how do receivers respond to the different situations?
urn:nbn:de:kobv:11-10047455
Keywords: C72; C92; 330; experiment; reciprocity; Trust; game